Safety and Security Engineering V 2013
DOI: 10.2495/safe130731
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on a non-seismic precast RC beam-column exterior joint under quasi-static lateral cyclic loading

Abstract: Beam-column joints were detected as the weakest link in existing RC momentresisting frames. The failure of beam-column joints, especially the exterior joint in a precast RC building commenced the collapse of the whole structure. Precast RC beam-column joints which were not designed in accordance with the seismic Code of Practice worsen the damage when subjected to seismic loading. This paper presents experimental work on a full-scale precast RC beam-column exterior joint with corbels when subjected to quasi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The yield displacement definition of experimental work is considered according to Ghani and Hamid [14] as shown in Figure 14. It was considered as the most practical definition for the yield displacement for the reinforced concrete structures.…”
Section: Load Deflection Behaviormentioning
confidence: 99%
“…The yield displacement definition of experimental work is considered according to Ghani and Hamid [14] as shown in Figure 14. It was considered as the most practical definition for the yield displacement for the reinforced concrete structures.…”
Section: Load Deflection Behaviormentioning
confidence: 99%
“…Previous research had highlighted that most of the RC structures components which have been designed such as beam-column joint with corbel, wall-slab connection, tunnel form building and precast shear-key wall performed poorly under in-plane lateral cyclic loading [1,2,3,4]. In order to improve the performance of beam-column joint in RC moment-resisting frames, fuse-bars which acting as energy dissipater will be installed inside the beam-column joint.…”
Section: Findings From Previous Researchmentioning
confidence: 99%
“…Most of existing RC buildings in Malaysia were designed in accordance to British Standard (BS 8110) which did not have any provision and guidelines for earthquake loading at all. Experimental works had been conducted for tunnel form building [1], non-seismic precast RC beam-column joint [2], wall-slab joints of Industrialized Building System (IBS) [3] and precast shear-key wall panel [4] which designed according to BS8110. The experimental results showed that the structural components performed poorly under in-plane and out-of-plane loading with low ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Layssi has studied the poor seismic response of shear walls and then repaired and retrofitted damaged walls using CFRP fabrics [11][12][13]. Others studies on shear walls and precast walls have been conducted in order to determine the seismic behavior of low-ductility precast walls under in-plane lateral cyclic loading [14][15][16][17]. Recently, strengthening techniques for non-ductile reinforced concrete shear walls using externally bonded CFRP sheets under in-plane seismic loading have been investigated [18,19].…”
Section: Introductionmentioning
confidence: 99%